2021
DOI: 10.1101/2021.01.29.428756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of urbanization and its environmental stressors on the intraspecific variation of flight functional traits in two bumblebee species

Abstract: Landscape anthropization replaces natural areas with either agricultural or urban covers, leading to land-use intensification. This worldwide phenomenon affects biodiversity, but little is known about the effects on the intraspecific variation of functional traits in spite of their importance for ecosystem functioning and services.Here we investigated if the functional traits of pollinator insects responded to land-use intensification and environmental stressors, by characterizing the variation of important tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 90 publications
(221 reference statements)
0
0
0
Order By: Relevance
“…This could occur through two different mechanisms: either higher temperatures may accelerate the larval development of the bees (Howe, 1967), or it could be an adaptation to hotter urban landscapes, in accordance with Bergmann's rule. The evidence supporting the body size-shrinking hypothesis in urban areas has been obtained at the intraspecific level in different species and countries: in Europe on different Bombus species (Apidae) (Theodorou et al, 2021;Tommasi et al, 2022), and in central America on two Euglossa species (Apidae) (Garlin et al, 2022). The variation in intertegular distance (proxy of body size) reached up to 5% in an approximate gradient of 10°C (Bombus terrestris, Theodorou et al, 2021).…”
Section: External Morphology Of Bees and The Uhi Effect 21 Body Sizementioning
confidence: 68%
See 1 more Smart Citation
“…This could occur through two different mechanisms: either higher temperatures may accelerate the larval development of the bees (Howe, 1967), or it could be an adaptation to hotter urban landscapes, in accordance with Bergmann's rule. The evidence supporting the body size-shrinking hypothesis in urban areas has been obtained at the intraspecific level in different species and countries: in Europe on different Bombus species (Apidae) (Theodorou et al, 2021;Tommasi et al, 2022), and in central America on two Euglossa species (Apidae) (Garlin et al, 2022). The variation in intertegular distance (proxy of body size) reached up to 5% in an approximate gradient of 10°C (Bombus terrestris, Theodorou et al, 2021).…”
Section: External Morphology Of Bees and The Uhi Effect 21 Body Sizementioning
confidence: 68%
“…The existing studies, however, yield contrasting results. For example, Tommasi et al (2022) found increasing FA in hotter urban areas in only one of the two Bombus species investigated, whereas Banaszak-Cibicka et al (2018) found no variation in wing asymmetry along an urbanization gradient in an Anthophora species. We note again that this contrasting evidence may be the result of the investigated species.…”
Section: Wing Morphometry and Flight Morphologymentioning
confidence: 92%